2014
DOI: 10.1111/jdi.12285
|View full text |Cite
|
Sign up to set email alerts
|

Heel bone strength is related to lifestyle factors in Okinawan men with type 2 diabetes mellitus

Abstract: Aims/IntroductionAlthough male diabetic patients have an increased risk of fracture, there is little information about this in the literature. The association between heel bone stiffness and the lifestyle of male patients with diabetes was evaluated.Materials and MethodsThe study included 108 participants with type 2 diabetes mellitus patients and 168 age-adjusted, healthy male volunteers. None of the participants had a history of osteoporosis or other severe diseases. Heel bone stiffness was examined by quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In a related study, findings were made that the effect of direct forces on bone formation was significantly better than indirect forces [ 2 ]. Although there are many existing studies based on the improvement of bone metabolism in T2DM by exercise, and several studies have focused on bone phenotypic indicators such as BMD and bone biomechanics [ 5 , 19 ], no related studies on the effects of different exercises on the expression of Wnt3a/β-catenin signalling pathway-related molecules and bone formation in T2DM mice have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…In a related study, findings were made that the effect of direct forces on bone formation was significantly better than indirect forces [ 2 ]. Although there are many existing studies based on the improvement of bone metabolism in T2DM by exercise, and several studies have focused on bone phenotypic indicators such as BMD and bone biomechanics [ 5 , 19 ], no related studies on the effects of different exercises on the expression of Wnt3a/β-catenin signalling pathway-related molecules and bone formation in T2DM mice have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…A related study found that the effect of direct forces on bone formation is signi cantly better than indirect forces (Akpinar et al, 2019). Although there are many studies on the improvement of bone metabolism in T2DM by exercise, and some studies have focused on bone phenotypic indicators such as BMD and bone biomechanics (Gushiken et al, 2015;Bello et al, 2014), related studies on the effects of different exercises on the expression of Wnt3a/βcatenin signalling pathway-related molecules and bone formation in T2DM mice have not been reported.…”
Section: Introductionmentioning
confidence: 99%